Meaning transference of prepositions of place "in, on and at" in english and the vietnamese equivalents / Ta Thi Thu Hien; Supervisor: Assoc. Prof. Dr Le Van Thanh - Ta, Thi Thu Hien
The thesis is based on the theory of empirical experience to analyze the meaning transferences of place prepositions “in, at and on” in English and equivalents in Vietnamese. To make a comparision between meaning transferences of prepositional of place “in, at and on” in English and in VietNamese or between those of English and their VietNamese equivalents. Thesis research is equivalent to the original meaning and the transformation is based on empirical rather than equivalent type words. From here, the thesis draws some conclusions about location orientation, location awareness of British and Vietnamese people through the use of prepositions. The sources of English language research materials are built on reference to bilingual dictionaries and monolingual dictionaries. Along with that is a reference to the official dictionary lookup pages of famous publishers. All English examples in this source are translated into Vietnamese based on dictionaries. The Vietnamese research language resource is built on the reference of monolingual and bilingual dictionaries. The thesis also uses linguistic materials collected on the internet. During the thesis implementation, I use some specific research methods: Method of analyzing the elemental meaning, Descriptive Method, Comparative method. The thesis will be one of the intensive researches on semantics and semantic change of some prepositions in English and equivalent expressions in Vietnamese from the perspective of cognitive linguistics. Based on the recent studies of cognitive linguistics, the thesis will add a significant amount of valuable information about the theoretical issues related to prepositions such as: personal experience and prepositions from place of view from the perspective of personal experience, the semantic change of place prepositions creates ray categories, ... the thesis will be a useful reference for those who are interested to the semantic theory of place prepositions viewed from the perspective of cognitive linguistics.